2004
DOI: 10.2337/diabetes.53.3.570
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Resistance and Enhancement of Feeding Facilitation by Melanin-Concentrating Hormone in Mice Lacking Bombesin Receptor Subtype-3

Abstract: Mice lacking either bombesin receptor subtype (BRS)-3 or gastrin-releasing peptide receptor (GRP-R) exhibit feeding abnormalities. However, it is unclear how these receptors are associated with feeding regulation. In BRS-3-deficient mice, we found hyperphagia, subsequent hyperleptinemia, and brain leptin resistance that occurred after the onset of obesity. To explore the cause of this phenomenon, we examined changes in feeding responses to appetite-related neuropeptides in BRS-3-deficient, GRP-R-deficient, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…In human cancer cells or cancers BB 3 receptors are not only ectopically expressed in a large number of tumors, as reviewed earlier (Fathi et al, 1993b(Fathi et al, , 1996Toi-Scott et al, 1996;Sun et al, 2000b;Reubi et al, 2002;Schulz et al, 2006), but their activation alters lung cancer behavior by increasing MAP kinase activation and nuclear oncogene expression ) and increasing adhesion of lung cancer tumor cells, which was proposed to contribute to increased tumor invasion and metastases by these tumors (Hou et al, 2006). In BB 3 knockout mice (Maekawa et al, 2004) the hyperphagic response to melanin-concentrating hormone (MCH) is impaired, but this impairment is not seen in BB 2 receptor knockout mice. Furthermore, the levels of the MCH receptor and prepro-MCH mRNAs in the hypothalamus of BB 3 receptor knockout mice were higher than those of controls, suggesting that up-regulation of the MCH receptor and MCH occurs in the knockout mice, which triggers hyperphagia and probably upsets the mechanism by which leptins decrease MCH receptors and feeding (Maekawa et al, 2004).…”
Section: Bb 3 Receptor In Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…In human cancer cells or cancers BB 3 receptors are not only ectopically expressed in a large number of tumors, as reviewed earlier (Fathi et al, 1993b(Fathi et al, , 1996Toi-Scott et al, 1996;Sun et al, 2000b;Reubi et al, 2002;Schulz et al, 2006), but their activation alters lung cancer behavior by increasing MAP kinase activation and nuclear oncogene expression ) and increasing adhesion of lung cancer tumor cells, which was proposed to contribute to increased tumor invasion and metastases by these tumors (Hou et al, 2006). In BB 3 knockout mice (Maekawa et al, 2004) the hyperphagic response to melanin-concentrating hormone (MCH) is impaired, but this impairment is not seen in BB 2 receptor knockout mice. Furthermore, the levels of the MCH receptor and prepro-MCH mRNAs in the hypothalamus of BB 3 receptor knockout mice were higher than those of controls, suggesting that up-regulation of the MCH receptor and MCH occurs in the knockout mice, which triggers hyperphagia and probably upsets the mechanism by which leptins decrease MCH receptors and feeding (Maekawa et al, 2004).…”
Section: Bb 3 Receptor In Diseasesmentioning
confidence: 91%
“…In BB 3 knockout mice (Maekawa et al, 2004) the hyperphagic response to melanin-concentrating hormone (MCH) is impaired, but this impairment is not seen in BB 2 receptor knockout mice. Furthermore, the levels of the MCH receptor and prepro-MCH mRNAs in the hypothalamus of BB 3 receptor knockout mice were higher than those of controls, suggesting that up-regulation of the MCH receptor and MCH occurs in the knockout mice, which triggers hyperphagia and probably upsets the mechanism by which leptins decrease MCH receptors and feeding (Maekawa et al, 2004). Studies of BB 3 receptor knockout mice suggest that this receptor is important in various behavioral effects, including the neural mechanisms that regulate social isolation (Yamada et al, 2000a), and are important in modulating emotion including forms of anxiety (Yamada et al, 2002a).…”
Section: Bb 3 Receptor In Diseasesmentioning
confidence: 99%
“…NMB was not effective in feeding suppression in mice. Central administration of bombesin also inhibit food intake in wild-type mice, but low dose was not effective in GRP-R-deficient mice (Maekawa et al, 2004b). Thus, for the regulation of food intake, GRP/GRP-R seems to be more important than NMB/NMB-R.…”
Section: Generation and Analysis Of Mice Lacking Each Receptor Subtypmentioning
confidence: 90%
“…i mRNA is observed in the early postnatal period, but not in adult animals. amount of food consumed and body weight were unchanged in GRP-R-deficient or in NMB-R-deficient mice compared with wild-type littermates, although old GRP-R-deficient mice showed slight increase in body weight (Wada et al, 1997;Hampton et al, 1998;OhkiHamazaki et al, 1999;Ladenheim et al, 2002;Maekawa et al, 2004b). It is demonstrated that this change was due to the increase of pellet consumed at each meal, but not the alteration of total amount of food consumed.…”
Section: Generation and Analysis Of Mice Lacking Each Receptor Subtypmentioning
confidence: 97%
See 1 more Smart Citation